Tax revenue planning method - Shparun, Dina V. (Journal of the Belarusian State University. Economics, 2018)
Address the issues of building the model of tax flows of the Republic of Belarus, taking into account the interaction between different economic actors. Submitted work scheduling method of tax revenues based on the modification of input – output table allows you to schedule tax flows in the national economy and analyse the impact of these changes on the dynamics of financial flows indicators of economic actors, analyze changes full costs of economic activities under different tax rates for selected economic activity, as well as tackle other tasks within the framework of tax policy State arising in forecasting and planning mechanisms of interaction of economic activities, i. e., linking macroeconomic and sectoral planning.